Does Financial Literacy Influence Students’ Level Of Consumptive Behavior?: The Moderating Role Of Self-Control - Febrina Ret Herdyane, Evelyn; Yoyok Soesatyo; Siti Sri Wulandari; Jun Surjanti (Technium Social Sciences Journal, 2024)
This research was conducted with the aim of analyzing the influence of financial literacy on students’ consumptive behavior with self-control as a moderating variable. The population in this study consisted of students who were studying economics for the 2020-2021 class at state universities in the province of East Java, Indonesia. Sampling used a purposive sampling method which resulted in 185 students. The analysis used in this research is the Structural Equation Model (SEM) which is supported by the Partial Least Method (PLS). The results of this research show that financial literacy has a negative and significant effect on consumptive behavior, and self-control is unable to moderate the influence of financial literacy on consumptive behavior. Therefore, it is important to only pay attention to financial literacy, but in its application it requires strong self-control in students so as not to direct their purchasing patterns towards consumptive behavior.